Prospective radiographic evaluation of peri-implant bone maintenance on osseointegrated implants with frictional morse taper connection and platform switching: Cases report (Research, Society and Development, 2021)
Objective: The aim of the present study was to evaluate radiographically the remodeling of the peri-implant bone crest in prosthetic friction morse cone implants, with platform switching, after 12 months of application of prosthetic load. Materials and Methods: 16 implants were installed, in 10 patients, rehabilitated with partial, single and multiple metal-ceramic prostheses, submitted to prosthetic function in the period of 12 months. Periapical radiographs to measure the distance between the mesial and distal marginal bone crest and the platform of each implant, were performed at the time of installing the prostheses and 12 months later. The images obtained at different intervals were digitized and analyzed using Image J software TD. Results: At the time of installing the prostheses, the averages of measurements on the distal and mesial surfaces were 0.57 mm (standard deviation 0.45) and 0.55 mm (standard deviation 0.41) respectively. After 12 months in function, the averages obtained were 0.59 mm (standard deviation 0.48) on the distal surface and 0.57 mm on the mesial surface, (standard deviation 0.34). Conclusion: In this radiographic evaluation, it was possible to observe that the implants with prosthetic connection of the frictional Cone Morse type with platform switching presented an average of 0.2mm of cervical bone remodeling, after 12 months in function, seeming to be a good alternative for periodic bone maintenance deploy.